ANALYSIS OF THE EFFECTIVENESS OF ONLINE LEARNING ON STUDENTS DURING THE PANDEMIC PERIOD COVID-19 AT UNIVERSITY MALIKUSSALEH - Muliaman, Agus; Wahdi Ginting, Fajrul (RADJA PUBLIKA, 2022)
The pandemic from the corona virus outbreak has paralyzed learning activities. Face-to-face learning cannot be done so that online learning is applied. The purpose of this research is to see the effectiveness of the learning process that has been going on so far. The place of this research is the Chemistry Education Study Program, Malikussaleh University with approximately 86 respondents as a sample of students. This research is quantitative research with survey method. The results of this study indicate that online learning is quite effective with a score of 3.21 (quite satisfied) but it is still far from being said to be effective with problems on the internet and health that burden students and lecturers, so that in the future most students (53.96%) are still more choose to take courses offline.